Longman business english usage - Strutt, Peter (Longman, 1998)
A reference designed for those who need to project a professional image through the accurate use of English. It contains 130 entries which include grammatical structures and key business vocabulary, focusing on the most commonly confused words. Examples are taken from a range of business fields. Each entry is followed by practice material. An answer key is included, making it suitable for self-study or classroom use.